An Unprecedented Blue Chromophore Found in Nature using a "Chemistry First" and Molecular Networking Approach: Discovery of Dactylocyanines A–H. Issue 58 (19th September 2017) - Bonneau, Natacha; Chen, Guanming; Lachkar, David; Boufridi, Asmaa; Gallard, Jean‐François; Retailleau, Pascal; Petek, Sylvain; Debitus, Cécile; Evanno, Laurent; Beniddir, Mehdi A.; Poupon, Erwan
Abstract: Guided by a "chemistry first" approach using molecular networking, eight new bright‐blue colored natural compounds, namely dactylocyanines A–H (3 –10 ), were isolated from the Polynesian marine sponge Dactylospongia metachromia . Starting from ilimaquinone (1 ), an hemisynthetic phishing probe (2 ) was prepared for annotating and matching structurally related natural substances in D. metachromia crude extract network. This strategy allowed characterizing for the first time in Nature the blue zwitterionic quinonoid chromophore. The solvatochromic properties of the latter are reported. Abstract : Blue‐eyed meroterpenes : Guided by a "chemistry first" approach using molecular networking, eight new bright‐blue‐colored natural compounds, namely dactylocyanines A–H bearing a zwitterionic quinonoid chromophore, were isolated from the Polynesian marine sponge Dactylospongia metachromia .